Relationship Between 5S Practices and Organizational Performance at Faber Medi-Serve Sdn. Bhd. - Rosni, Suib (2011)
Based on the Japanese words Seiri, Seiton, Seiso, Seiketsu and Shitsuke, the 5s philosophy focuses on effective workplace organization and standardized work procedures. Once fully implemented, the 5s practices can increase moral, create positive impressions on customer, increase efficiency and organization. Not only employee will feel better about where they work, but the continuous improvement of 5s leads to less waste, better quality and faster lead time. 5s practice is one of the techniques to improve quality environment, health and safety at the workplace. This study is carried out to identify the relationship between 5s implementation and performance at Faber Medi-Serve Sdn. Bhd. This study intends to identify whether the practice had improved the performance of the company and this is important as to extend the government (MOH) contract. The scope of study covers the area of six locations ie. FMS Kuala Nerang Tuanku Fauziah, Jitra, Yan, Sik, Baling and Sungai Bakap. A total of 140 sets of questionnaires were distributed. Out of 122 sets were returned and it takes about two weeks to complete the questionnaires by respondents. The data analyzed by using SPSS version 12. This study also explains the process of 5s implementation at the company.